PRAGMATIC GOAL AND METHODS OF HEALTHY LIFESTYLE REPRESENTATION IN SPANISH PUBLICISM - Shramko , Alona (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is dedicated to the study of the pragmatic goals and methods used in Spanish media in order to represent healthy lifestyle and introduce certain ideas into society concerning stated topic. We have examined the definition of term “communicative strategy” and “communicative tactic” in the scientific works of Ukrainian and foreign linguists. Besides, the role of pragmatics in modern linguistics has been analyzed. We have studied the classification of communicative strategies suggested by Ukrainian scientists. Furthermore, we have proposed our own classification of communicative tactics used in the informing and prevention strategies to make sure people get information about negative consequences of being overweight and prevent this and other diseases. The practical basis of our research includes following communicative tactics: the tactic of facts usage and references to the opinion of authorities, the tactic of persuasion , the tactic of explanation, the tactic of a genuine dialogue formation with the reader. We have analyzed who of the Ukrainian and foreign scientists have made great contribution into the study of stated topic. We have examined three components of a communicative strategy, which are essential for its formation. Last but not least, the practical usage of obtained results have been analyzed as well as opportunities for further research in stated field.__________References:• Bacevych, F. S. Osnovy komunikatyvnoi' lingvistyk: pidruchnyk [The basis of communacative linguistics: manual] (Kyi'v: Akademija, 2004), 342.• Bjelova, A. D. «Komunikatyvni strategii' i taktyky: problemy semantyky.» Movni i konceptual'ni kartyny svitu [«Communicative strategies andtactics: problems of semantics.» Language and conceptual world image] 10 (2004): 11–16.• Boboshko, T. M. Komunikatyvni strategii' i taktyky v ocinnyh vyslovlennjah adresata [Communicative strategies and tactics in evalustive statements of addressee] (2013), https://www.researchgate.net/publication/315099574_Komunikativni_strategii_i_taktiki_ta_ocinni_vislovlenna.• Stanko, D. V. «Strategii' i taktyky v emocijnomu movlenni» [«Strategies and tactics in emotional speech»]. Zapysky z romano-germans'koi' filologii' 1 (2014).• Dan, S., Deirdre, W. Pragmatics (Cambridge University Press, 2012): 1–27.• Elvis, F., Héverd, A., Jairo, F. Estrategias de comunicación: diseño, ejecución y seguimiento (Estados Unidos, 2020), 84.• Julia, Díez. Así es cómo los anuncios de dulces perjudican la salud de los niños https://elpais.com/salud-y-bienestar/nutrir-con-ciencia/2022-06-09/asi-es-como-los-anuncios-de-dulces-perjudican-la-salud-de-los-ninos.html• Julia, Díez. La obesidad no es un problema solo para nutricionistas, https://elpais.com/salud-y-bienestar/nutrir-con-ciencia/2022-08-01/la-obesidad-no-es-un-problema-solo-para-nutricionistas.html• Leech, G. N. Principles of pragmatics (London; New York: Longman, 1983), 250.• Silvia Valtueña Martínez, Ana M. Rincón. Aditivos, propiedades saludables y fechas de caducidad: guía para entender las etiquetas alimentarias, https://elpais.com/salud-y-bienestar/nutrir-con-ciencia/• Victorino, Z. La danza de los signos (2002), 243.
Keywords: pragmatics, communicative strategy, communicative tactic, communication, aspects of communicative situation, communicative intention, components of communicative strategy